Cerebral hemodynamics evaluation of FLAIR vascular hyperintensity in TIA patients with large artery severe stenosis or occlusion - Zeng, Lichuan; Wang, Jiamei; Wang, Qu; Zhang, Yaodan; Liao, Huaqiang; Wu, Wenbin (Frontiers in Neurology, 2025)
PurposeTo assess the practicality and utility of employing dual post-label delay (PLD) arterial spin labeling (ASL) in transient ischemic attack (TIA) individuals exhibiting Fluid-attenuated inversion recovery (FLAIR) vascular hyperintensity (FVH).Materials and methodsWe conducted a retrospective review of clinical data from TIA patients presenting with unilateral severe atherosclerotic stenosis or obstruction of either the intracranial internal carotid artery or the middle cerebral artery. Participants were categorized into two groups based on the presence or absence of FVH: FVH positive and FVH negative. All individuals underwent pseudo-continuous ASL perfusion imaging, utilizing distinct PLD durations (1,525 and 2,525 ms) alongside qualitative visual assessments of ASL perfusion irregularities. Standardized TIA evaluations, which included medical history reviews, neuropsychological assessments, and ABCD2 scoring, were performed on all subjects. We explored the correlations between FVHs, clinical manifestations, vascular risk factors, and perfusion metrics.ResultsA total of 50 patients were included in this investigation, with FVH detected in 16 subjects (32.0%). The ABCD2 score was notably elevated within the FVH positive cohort compared to the FVH negative group. At a PLD of 1,525 ms, cerebral blood flow (CBF) values for the affected and healthy hemispheres in the FVH positive group were recorded at 19.55 ± 6.67 and 40.32 ± 6.83, respectively; corresponding values in the FVH negative group were 23.74 ± 5.03 and 46.43 ± 7.91. For a PLD of 2,525 ms, the CBF values for the affected and healthy sides in the FVH positive group were 34.11 ± 5.87 and 50.27 ± 8.57, while the FVH negative group recorded values of 42.79 ± 7.03 and 52.07 ± 7.29, respectively. The differential CBF (ΔCBF) for the affected side in the FVH positive and negative groups was 14.57 ± 4.34 and 19.05 ± 6.10, respectively. A significant negative correlation was established between ΔCBF and ABCD2 scores (Kendall’s tau-b = −0.578, p < 0.001).ConclusionThe findings of this study indicate a strong association between the presence of FVH signs and a marked reduction in cerebral blood flow, as well as diminished blood flow reserve. This underscores the potential role of FVH as a biomarker for hemodynamic impairment in TIA patients.